Olympic and modern games - Kirkwood, Mildred I. (My University, 1905)
Introduction: At the present time, physical training and the games of various sorts are attracting more general attention than at any previous time. This awakening of the people to the delights of this nature, together with an increased intelligence of acquiring a strong and beautiful body both for use and ornament, makes necessary a corresponding knowledge of the practical laws of health and the relation proper food, sleep, bathing and clothing as well as exercise to the welfare of the body. Especially are college authorities beginning to recognize the true relation of the body and mind and to value athletic games as an aid to the best intellectual activity. The abounding health, grace of motion and dignity of bearing of the athlete is also causing an increased appreciation of physical beauty. The Olympic games were the most famous of the four great national festivals of the Greeks. They were celebrated in the sanctuary of Zeus at Olympia, a beautiful valley in the Pisatis, the southeastern district of Elis, at the junction of the Cladeus with the Alpheus.
Citation: Kirkwood, Mildred I. Olympic and modern games. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Qlympic Games; Modern Games; Theses; Manuscripts (documents)